„Katechizm za sześć centów…” Jan kardynał Puzyna wobec kwestii socjalnej - Marchel, Sławomir (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
In the polish historiography of the nineteenth century the Catholic hierarchs are seen primarily as representatives of the conservative authorities, inhibiting the development of new forms of social life. In fact, with few exceptions, changes in the relations between social classes and within each of them, have been taking by them with a strong reserve, and even resentment. In the most expressive way it was reflected in relation to the situation of the lower social classes, that in the second half of the century, begun to occupy an important place in the arena of European civilization’s transformation. In this context, an interesting example would be for researchers activities of Jan Puzyna, prince, bishop and cardinal. The controversy, which over the years has been accumulated around his person, caused that today is identified of the most negative features of Polish Catholicism. However, while the creation of such assessments, has its justification in the essence of collective memory, it is the duty of the historian to verify it.